Nephrotoxicity of cancer therapeutic drugs: Focusing on novel agents - Min Hee Hong (The Korean Society of Nephrology, 2021)
Kidney injury caused by anticancer agents is a common problem that can interfere with and affect the dose intensity of anticancer therapy, thus restricting patient survival. Recent advances in targeted and immunotherapeutic agents have transformed the landscape of medical oncology, and these agents have been widely employed in clinical practice. While typically associated with favorable toxicity profiles, several novel anticancer drugs present distinctive nephrotoxicities. It remains urgent to closely monitor renal injuries associated with these agents, and medical practitioners should be familiar with general principles for managing nephrotoxicity associated with novel cancer drugs. This review provides an in-depth investigation of the literature and guidelines regarding the prevalence, clinical presentations, mechanisms, and management of nephrotoxicity for each drug.